x 4 + x 3 + x 2 + x + 1 = 0
Solve for x in the equation above. If x = f a ± b ± i c ± d e , find ∣ a + b + c + d + e + f ∣ .
HInt: Look at the title.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used Descartes's method, which can be used to solve any general quartic equation x 4 + a x 3 + b x 2 + c x + d = 0 . First obtain the depressed quartic by making the substitution x = y − 4 a . (A depressed quartic is a quartic with no cube term.) For this problem, this results in y 4 + 8 5 y 2 + 8 5 y + 2 5 6 2 0 5 = 0 . With no cube term, the quartic can be factorized into the form ( y 2 + k y + m ) ( y 2 − k y + n ) . Equating the coefficients leads to the system of equations: m + n − k 2 = 8 5 k ( n − m ) = 8 5 m n = 2 5 6 2 0 5 I solved the system in the following way: Divide by k in the second equation, then add it to the first. This results in: 2 n = k 2 + 8 5 ( 1 + k 1 ) Then divide by k again in the second equation and subtract the first and second to obtain: 2 m = k 2 + 8 5 ( 1 − k 1 ) Then multiply the two resulting equations: 4 m n = 6 4 2 0 5 = ( ( k 2 + 8 5 ( 1 − k 1 ) ) ( k 2 + 8 5 ( 1 + k 1 ) ) = k 4 + 4 5 k 2 + 6 4 2 5 ( 1 − k 2 1 ) ⇒ 6 4 k 6 + 8 0 k 4 − 1 8 0 k 2 − 2 5 = 0 Using the rational zeros theorem, one can find k 2 = 4 5 as a possible solution. I will use k = 2 5 . This leads to n = 1 6 1 5 + 8 5 and m = 1 6 1 5 − 8 5 . Applying the quadratic formula on the two equations: y 2 + 2 5 y + 1 6 1 5 − 8 5 = 0 y 2 − 2 5 y + 1 6 1 5 + 8 5 = 0 one gets y = 4 − 5 ± i 1 0 + 2 5 and y = 4 5 ± i 1 0 − 2 5 . Then remember to subtract 4 1 (since x = y − 4 1 ) to get the final answer: x = 4 − 1 − 5 ± i 1 0 + 2 5 , 4 − 1 + 5 ± i 1 0 − 2 5 And, therefore, a + b + c + d + e + f = − 1 + 5 + 1 0 + 2 + 5 + 4 = 2 5 = 5 . One might also want to note that these are the fifth roots of unity (other than 1).
Problem Loading...
Note Loading...
Set Loading...
x 4 + x 3 + x 2 + x + 1 = 0 The coefficients of this quartic equation are symmetrical, so we can do a neat trick by factoring out an x 2 and getting everything in terms of ( x + x − 1 ) : x 2 [ x 2 + x + 1 + x − 1 + x − 2 ] = 0 x 2 [ ( x 2 + 2 + x − 2 ) + ( x + x − 1 ) − 1 ] = 0 x 2 [ ( x + x − 1 ) 2 + ( x + x − 1 ) − 1 ] = 0 Here, we can use the quadratic formula to get the roots and factorise. Most textbook questions would give tidy results, but unfortunately this ends up fairly messy: ( x + x − 1 ) = 2 ( 1 ) − ( 1 ) ± 1 2 + 4 ( 1 ) ( 1 ) = 2 − 1 ± 5 x 2 ( x + x − 1 − 2 − 1 − 5 ) ( x + x − 1 − 2 − 1 + 5 ) = 0 x 2 ( x + 2 1 + 5 + x − 1 ) ( x + 2 1 − 5 + x − 1 ) = 0 Then we can redistribute one half of the x 2 into the first bracket and the other into the second, resulting in two quadratic equations: ( x 2 + 2 1 + 5 x + 1 ) ( x 2 + 2 1 − 5 x + 1 ) = 0 We could have substituted x for c i s θ and simplified this with trigonometry, but looking at the answer required, quadratic formula is probably more direct.
I will multiply everything by 2 to remove annoying fractions, then use quadratic formula one more time: x 2 + 2 1 ± 5 x + 1 = 0 2 x 2 + ( 1 ± 5 ) x + 2 = 0 x = 2 ( 2 ) − ( 1 ± 5 ) ± ( 1 ± 5 ) 2 − 4 ( 2 ) ( 2 ) = 4 − 1 ± 5 ± 1 ± 2 5 + 5 − 1 6 = 4 − 1 ± 5 ± − 1 0 ± 2 5 = 4 − 1 ± 5 ± i 1 0 ± 2 5 So we get a = − 1 , b = 5 , c = 1 0 , d = 2 , e = 5 , f = 4 . This means our final answer is: − 1 + 5 + 1 0 + 2 + 5 + 4 = 2 5 = 5